Ethnomedicinal appraisal and conservation status of medicinal plants among the Manobo tribe of Bayugan City, Philippines - MARK LLOYD G. DAPAR; ULRICH MEVE; SIGRID LIEDE-SCHUMANN; GRECEBIO JONATHAN D. ALEJANDRO (Society for Indonesian Biodiversity, 2020)
Abstract. Dapar MLG, Meve U, Liede-Schumann S, Alejandro GJD. 2020. Ethnomedicinal appraisal and conservation status of medicinal plants among the Manobo tribe of Bayugan City, Philippines. Biodiversitas 21: 3843-3855. Manobo tribe is one of the most populated indigenous communities in the Philippines clustered in various parts of Mindanao archipelago with distinct cultural traditions and medicinal practices. This study aims to document the Agusan Manobo tribe medicinal plant uses and knowledge and to assess the conservation status of their medicinal plants found in upland ancestral lands where ethnomedicinal practices still prevail. Ethnomedicinal data were gathered from 95 key informants through semi-structured interviews, focus group discussions, and guided field walks in five selected upland barangays of Bayugan City. Family importance value (FIV) and relative frequency of citation (RFC) were quantified. The conservation status of their medicinal plants was assessed based on the international and national listing of threatened species. A total of 90 species belonging to 82 genera and 41 families were identified as ethnomedicinally important. Highest FIV (98.9) was reported for Piperaceae in treatment for skin diseases and infections. The most cited medicinal plant species was Piper decumanum L. (RFC=0.95), which is primarily used in treatment for insect and snake bites. Conservation assessment revealed that the five upland areas of the Agusan Manobo tribe are habitats of endemic, endangered, vulnerable and threatened species. The results of this study present the rich ethnomedicinal knowledge of Agusan Manobo cultural community, which could serve as a useful source of information to improve community healthcare and environmental conservation and management. Local people and the government should actively participate in shared management responsibilities for viable conservation strategies and sustainable use of the cultural community resources.